Family Business in India: Performance, Challenges and Improvement Measures. Issue 1 (June 2020) - Chahal, Himani; Sharma, Anil K.
Existing literature on family businesses brings out their significance globally. The prevalence of family businesses is a phenomenon that is universal and found in most countries worldwide, although their relative impact on economies does vary. This article reviews papers in the accounting and finance literature on family businesses around the world and shows that the involvement of family members in the business may have a positive, negative or no impact on its financial performance. In the Indian context, the literature review indicates that India's rich and ancient history seems to be interrelated with the family-run businesses as the principal means of business organization. The paper gives a glimpse of the status of family businesses in India since independence and the distinct characteristics of Indian family businesses. In the next section, we try to find out how family firms are performing in India in comparison to non-family firms by studying companies listed in the National Stock Exchange of India Ltd. (NSE) 500 Index for a period of 5 years ranging from 2014 to 2018. The results show that family businesses are not performing significantly better than non-family firms in the Indian business scenario. We try to highlight the reasons for the same by underlining the issues faced by family businesses and suggest measures to overcome these issues. The study concludes with a discussion on the lessons that new family business ventures can take from family business groups in India that have made a mark in the Indian and the world business scenario because of their ability to face and successfully overcome challenges faced by family firms.